Developing ELT materials for muslim learners: a qualitative study - Preece, Abdul Shakour (Institute of Education, International Islamic University Malaysia, 2011)
The purpose of this study is to address the gap that exists in the ELT materials market by developing 'Islamised ELT materials' for Muslim learners. However, before this could be done, it was necessary to identify the meaning of Islamisation of ELT and to consider why it is necessary. A critical analysis of existing Islamised ELT materials and syllabuses was conducted, along with a review of the literature on general curriculum theory, ELT curriculum theory and Islamic worldview. This information was then synthesised into a framework for the production of Islamised ELT materials. Next, a sample of ELT materials for Muslim learners (EMML) was prepared in accordance with the framework that combined Islamic content with stories containing philosophical concepts. The sample was then administered to a class of CELPAD students using an instructional method known as 'community of inquiry', pioneered by Mathew Lipman for teaching philosophy in schools (P4C). The researcher used qualitative data collection instruments, during and after the implementation, to evaluate the materials. In addition, a qualitative research software known as Nvivo was used to store and code the data. After this, the data was analysed using 'content analysis' to reveal students' responses and reactions to the materials. The researcher engaged two inter-raters from the fields of ELT and education to corroborate the findings. The discussion section looks at language acquisition and the advantages of teaching for meaning, as well as the pros and cons of teaching grammar and vocabulary in-context. The conclusion of the study begins by summarising the advantages of EMML for Muslim learners such as: motivation to study English, promotion of critical thinking skills, affecting students' feelings about the Islamic content of the lessons and the benefits for students' English. The main implication of the study was that the Islamic content, philosophical inquiry and stories of EMML were meaningful and motivating for Muslim learners, thereby enhancing their English language learning. The study ends by recommending ways to improve the design and implementation of EMML in the ELT classroom. It also highlights the need to rethink curriculum design and assessment procedures in Muslim ELT institutions seeking to employ EMML. Lastly, the study recommends that further research be conducted in the area of language acquisition and EMML.